Deliberate and contextual learning of L2 idioms: The effect of learning conditions on online processing. (April 2021) - Obermeier, Andrew; Elgort, Irina
Abstract: This research compares the outcomes of two computer-assisted second language (L2) idiom learning conditions: deliberate and contextual. Low-intermediate proficiency Japanese learners of English studied 36 idioms online by either using flashcards or reading them in sentences with contextual clues to their meanings over three learning sessions. Posttest results of these two learning conditions were compared with each other and with a baseline condition in which no learning occurred. In an idiom translation posttest, L2 participants showed superior declarative knowledge of the idioms learned in the flashcard condition. Nondeclarative knowledge gains were measured on a self-paced reading (SPR) task validated in a pilot study with 60 native (L1) readers. Although the idioms primed semantic probes during reading for the L1 participants, this was not the case for the L2 learners. Nevertheless, the two learning conditions had some positive effects on the semantic probes compared to the baseline. The finding that participants had fluent access to the idioms' figurative meanings while reading the semantic probes is particularly important for the flashcard condition because it suggests that this learning approach results in knowledge relevant in real-time language use.